A case report of healthcare-associated psittacosis - Deng, Fei; Lin, Qibin; Xu, Xiaohong; Li, Changsong; Xu, Jianbo; Nie, Hanxiang (The Journal of Infection in Developing Countries, 2023)
Introduction: Psittacosis is a well-recognized zoonotic infectious disorder caused by Chlamydia psittaci (C. psittaci). Human-to-human transmission of C. psittaci has rarely been reported previously, especially in the case of healthcare-associated infections. Case report: A 32-year-old man was admitted to the intensive care unit with severe pneumonia. An intensive care unit healthcare worker contracted pneumonia 7 days after performing endotracheal intubation on the patient. The first patient, a duck feeder, had been closely exposed to ducks, while the second patient had not been exposed to any birds, mammals or poultry. C. psittaci sequences were obtained by metagenomic next-generation sequencing analyses of bronchial alveolar lavage fluid of both the patients, and they were diagnosed with psittacosis. Therefore, healthcare-associated human-to-human transmission between both cases took place. Conclusions: Our findings have implications for managing patients with suspected psittacosis. stringent protective measures are needed to prevent healthcare-associated human-to-human transmission of C. psittaci.